Bothrops asper snake venom and its metalloproteinase BaP–1 activate the complement system. Role in leucocyte recruitment. Issue 5 (2000) - Farsky, Sandra H. P.; Gonçalves, Luís Roberto C.; Gutiérrez, José M.; Correa, Adriana P.; Rucavado, Alexandra; Gasque, Philippe; Tambourgi, Denise V.
Abstract : The venom of the snake Bothrops asper, the most important poisonous snake in Central America, evokes an inflammatory response, the mechanisms of which are not well characterized. The objectives of this study were to investigate whether B. asper venom and its purified toxins – phospholipases and metalloproteinase – activate the complement system and the contribution of the effect on leucocyte recruitment. In vitro chemotaxis assays were performed using Boyden's chamber model to investigate the ability of serum incubated with venom and its purified toxins to induce neutrophil migration. The complement consumption by the venom was evaluated using an in vitro haemolytic assay. The importance of complement activation by the venom on neutrophil migration was investigated in vivo by injecting the venom into the peritoneal cavity of C5-deficient mice. Data obtained demonstrated that serum incubated with crude venom and its purified metalloproteinase BaP–1 are able to induce rat neutrophil chemotaxis, probably mediated by agent(s) derived from the complement system. This hypothesis was corroborated by the capacity of the venom to activate this system in vitro . The involvement of C5a in neutrophil chemotaxis induced by venom-activated serum was demonstrated by abolishing migration when neutrophils were pre-incubated with antirat C5a receptor antibody. The relevance of the complement system in in vivo leucocyte mobilization was further demonstrated by the drastic decrease of this response in C5-deficient mice. Pre-incubation of serum with the soluble human recombinant complement receptor type 1 (sCR 1) did not prevent the response induced by the venom, but abolished the migration evoked by metalloproteinase-activated serum. These data show the role of the complement system in bothropic envenomation and the participation of metalloproteinase in the effect. Also, they suggest that the venom may contain other component(s) which can cause direct activation of C5a.